Quantification methods of Candida albicans are independent irrespective of fungal morphology - Soares, Amanda B. [UNESP]; de Albuquerque, Maria C. [UNESP]; Rosa, Leticia M. [UNESP]; Klein, Marlise I.; Pavarina, Ana C. [UNESP]; Barbugli, Paula A. [UNESP]; Dovigo, Livia N. [UNESP]; de O Mima, Ewerton G. [UNESP] (Shared Science Publishers OG, 2024)
The ability of Candida albicans to switch its morphology from yeast to filaments, known as polymorphism, may bias the methods used in microbial quantification. Here, we compared the quantification methods [cell/mL, colony forming units (CFU)/mL, and the number of nuclei estimated by viability polymerase chain reaction (vPCR)] of three strains of C. albicans (one reference strain and two clinical isolates) grown as yeast, filaments, and biofilms. Metabolic activity (XTT assay) was also used for biofilms. Comparisons between the methods were evaluated by agreement analyses [Intraclass and Concordance Correlation Coefficients (ICC and CCC, respectively) and Bland-Altman Plot] and Pearson Correlation (α = 0.05). Principal Component Analysis (PCA) was employed to visualize the similarities and differences between the methods. Results demonstrated a lack of agreement between all methods irrespective of fungal morphology/growth, even when a strong correlation was observed. Bland-Altman plot also demonstrated proportional bias between all methods for all morphologies/growth, except between CFU/mL X vPCR for yeasts and biofilms. For all morphologies, the correlation between the methods were strong, but without linear relationship between them, except for yeast where vPCR showed weak correlation with cells/mL and CFU/mL. XTT moderately correlated with CFU/mL and vPCR and weakly correlated with cells/mL. For all morphologies/growth, PCA showed that CFU/mL was similar to cells/mL and vPCR was distinct from them, but for biofilms vPCR became more similar to CFU/mL and cells/mL while XTT was the most distinct method. As conclusions, our investigation demonstrated that CFU/mL underestimated cells/mL, while vPCR overestimated both cells/mL and CFU/mL, and that the methods had poor agreement and lack of linear relationship, irrespective of C. albicans morphology/growth.
Keywords: Candida albicans; cell count; colony count; hyphae; microbial; polymerase chain reaction; yeasts